Anaphoric And Cataphoric References in The Novel The Kite Runner - Waladdin Panggabean; Khusnul Khatimah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
On the basis of the case, the researcher is interested in learning about the literary references created in works such as the novel The Kite Runner, which is being studied. When preparing for a TOEFL or other English language proficiency test, the researcher believes that references will be required to clarify the comprehension obtained in the novels studied as part of the degree program. The research examines the novel The Kite Runner's anaphoric and cataphoric references. The research method used is qualitative, and the theory is Yule's theory of pragmatics, which is used to analyze the novel's anaphoric and cataphoric references. The researcher employs qualitative research methods because the data for this study are restricted to words or phrases that appear in the novel The kite runner. The purpose of this research is to examine the novel's references. The novel contains 19 anaphoric and 9 cataphoric references.